Digital Marketing Services Enhance Business Performance Goals by Promoting Products and Services to Consumers: A Digital Approach - Zaheer, Asma (British Journal of Marketing Studies, 2020)
The study focus on determining the effect of Digital Essentials tools for promoting products and services to enhance business performance. The digital marketing SMART objectives benchmarked against the existing competitors to ensure effectiveness for achieving the organizational goals. Digital marketing mix utilises marketing techniques, lead generation, social media and website optimization. Digital essentials include targeting and cost effectiveness to promote the product to the needy people at the proper time. Facebook page and QR codes have more influence on the consumer’s behavior as a marketing tool. Content plays very important role for website in attracting potential customers in near future and Flow content is very useful for acquisition and amplification. There are many issues related to online purchase, but the most important concerns of the buyers/customers are: cancellation and refund. Therefore, an organization takes special interest in sorting out such issues. In conclusion the digital essential tools effect business p and promote products and services.